2020
DOI: 10.1002/lary.29068
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Glottic Gap and Voice Impairment in Presbyphonia

Abstract: Objective/Hypothesis The objective of this study was to investigate the glottic gap area as a significant marker for the severity of presbyphonia as it relates to patient‐reported outcome measures (Voice Handicap Index‐10 [VHI‐10]) and stroboscopic findings. Study Design Retrospective case‐control study conducted in an academic tertiary voice center. Methods Patients seen at a tertiary voice clinic who were diagnosed with presbyphonia without other organic laryngeal pathology from January 2014 to December 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
1
4
0
1
Order By: Relevance
“…failed to demonstrate a correlation between glottic gap area and Voice Handicap Index-10. 5,16,17 Our results showed that patients with presbylarynx had higher Voice Handicap Index-30 total scores, as well as higher functional, physical and emotional subdomain scores, which was also reported by Santos et al . 4 Moreover, if a spindle-shaped glottal gap was present, Voice Handicap Index scores were even higher.…”
Section: Discussionsupporting
confidence: 88%
“…failed to demonstrate a correlation between glottic gap area and Voice Handicap Index-10. 5,16,17 Our results showed that patients with presbylarynx had higher Voice Handicap Index-30 total scores, as well as higher functional, physical and emotional subdomain scores, which was also reported by Santos et al . 4 Moreover, if a spindle-shaped glottal gap was present, Voice Handicap Index scores were even higher.…”
Section: Discussionsupporting
confidence: 88%
“…Few studies focus exclusively on elderly patients with presbyphonia. McGarey et al 23 evaluated the glottic gap but not treatments. Hsiung and Pai 31 and van den Broek et al 37 evaluated AAI but included patients aged <30 years.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting area was measured with the rod tool. This measurement technique is similar to the mechanism used by Woo 22 and McGarey et al 23 to measure the waveform of the glottic area during videostroboscopy.…”
Section: Methodsmentioning
confidence: 99%
“…The inability to achieve any phonation in our animal model is associated with large glottic gaps. For each rabbit, the lengthcorrected unilateral maximal glottal area [21][22][23][24][25] (MGA) (Fig. 3c), representing glottic insufficiency, was subtracted from the bilateral MGA to give an area difference.…”
Section: Quantification Of Functional Vocal Fold Augmentationmentioning
confidence: 99%